A Possibility of Real Time Earthquake Magnitude Determination using GPS for Tsunami warning System in Indonesia - Sulastri Sulastri; Buldan Muslim; Bambang Sunardi; Supriyanto Rohadi; Yusuf Hadi Perdana; Muzli Muzli; Susilo Susilo; Jonny Effendi (Jurnal Sains Dasar, 2018)
This paper contains preliminary study about the possibility of real time earthquake magnitude determination from GPS in Indonesia for tsunami warning system. Until now, the determination of earthquake sources in Indonesia by using seismic records. By a collaborative research and utilizing the GPS networks managed by Indonesian Geospatial Information Agency (Badan Informasi Geospasial/ BIG), there is a chance to determine the earthquake magnitude in another way, instead of using seismograph and accelerograph networks. The displacement vector from GPS measurements plays important rules in the earthquake magnitude determination. In the future, the earthquake magnitude determination using GPS could support the Indonesia Tsunami Early Warning System conducted by BMKG.